2000
DOI: 10.1097/00005768-200007000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Human erythrocyte and plasma amino acid concentrations during exercise

Abstract: These results highlight that far from being slow in the uptake of amino acids, the erythrocyte in fact sequesters amino acids at an appreciable rate during exercise without a corresponding elevation in the plasma amino acids. For a greater understanding of amino acid changes during exercise, the analysis of both plasma and erythrocytes is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Thus, significant equivalent increases of 10% in plasma tHcy have been observed 30 min after running on a treadmill (39) or 19% in marathon runners 24 h after finishing the race (22). Resting plasma amino acid concentrations were within the range of previously reported values (17). These resting concentrations varied significantly between sports and differences may be due to minor variations in protein content of the diet before the overnight fast and to different body mass index or physical training.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, significant equivalent increases of 10% in plasma tHcy have been observed 30 min after running on a treadmill (39) or 19% in marathon runners 24 h after finishing the race (22). Resting plasma amino acid concentrations were within the range of previously reported values (17). These resting concentrations varied significantly between sports and differences may be due to minor variations in protein content of the diet before the overnight fast and to different body mass index or physical training.…”
Section: Discussionsupporting
confidence: 66%
“…It was shown that erythrocytes and plasma have very different profile characteristics where at least eight amino acids were measured at significantly higher levels in the erythrocytes than the corresponding plasma and two amino acids (glutamine and arginine) were found to be lower (p < 0.01) (Agli et al 1998). Aspartic acid showed contrasting levels in erythrocytes and plasma analysed from resting blood samples, with 451-484 µM in the erythrocytes compared with 14.5-15.1 µM in the corresponding plasma (MacLaren et al 2000).…”
Section: Introductionmentioning
confidence: 88%
“…Amino acid levels in human plasma and erythrocytes were found to increase significantly in the post-absorptive state following an oral loading of amino acids (Agli et al 1998). A separate study in a human exercise challenge demonstrated that erythrocytes increased their carrying capacity of amino acids during exercise with no corresponding change in the plasma levels (MacLaren et al 2000). These investigations have made important and relevant contributions providing evidence that the amino acid concentrations in erythrocytes are acutely sensitive to lifestyle interventions and alter post-absorption or in response to exercise.…”
Section: Introductionmentioning
confidence: 94%
“…[1][2][3][4][5][6] For over thirty years most amino acid analyses have been performed by ion-exchange chromatography with post-column derivatization with ninhydrin. [7] Alternatively, amino acids can be analyzed by precolumn fluorescent derivatization and then separated by reverse-phase high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%